The dog that barks doesn't bite: Coverage and compliance of sectoral minimum wages in Italy - Andrea Garnero (IZA Journal of Labor Policy, 2018)
This paper provides a comprehensive portrait of the level and compliance with sectoral minimum wages in Italy between 2008 and 2015. The results show that wage floors in Italy are relatively high both in absolute terms and relative to the median wage. However, non-compliance rates are not negligible: on average, around 10% of workers are paid 20% less than the minimum wage established in their reference collective agreement. Non-compliance is particularly high in the South and in micro and small firms, and it affects especially women and temporary workers. Overall, wages in the bottom of the distribution appear to be largely unaffected by minimum wage increases. More effective enforcement practices are therefore needed to safeguard a level playing field for firms and ensure that minimum wage increases are effectively reflected in pay increases for workers at the bottom of the distribution.
Keywords: J08; J31; J52; J83; 330; Minimum wages; Collective bargaining; Compliance